Physical characterization of the active asteroid (6478) Gault. Issue 4 (23rd July 2021) - Carbognani, Albino; Buzzoni, Alberto; Stirpe, Giovanna
ABSTRACT: We report dense light-curve photometry, BVRc colours and phase–mag curve of (6478) Gault, an active asteroid with sporadic comet-like ejection of dust. We collected optical observations along the 2020 July–November months during which the asteroid appear always star-like, without any form of perceptible activity. We found complex light curves, with low amplitude around opposition and a bit higher amplitude far opposition, with a mean best rotation period of 2.46±0.02 h. Shape changes were observed in the phased light curves after opposition, a probable indication of concavities and surface irregularities. We suspect the existence of an Amplitude–Phase Relationship in C band. The mean colours are B − V  = +0.84±0.04, V − Rc  = +0.43±0.03, and B − Rc  = +1.27±0.02, compatible with an S-type asteroid, but variables with the rotational phase index of a non-homogeneous surface composition. From our phase–mag curve and Shevchenko's empirical photometric system, the geometric albedo result pV  = 0.13±0.04, lower than the average value of the S-class. We estimate an absolute mag in V band of about  + 14.9 and this, together with the albedo value, allows us to estimate a diameter of about 3–4 km, so Gault may be smaller than previously thought.